2008
DOI: 10.1007/s10648-008-9080-9
|View full text |Cite
|
Sign up to set email alerts
|

Self-Regulation of Learning within Computer-based Learning Environments: A Critical Analysis

Abstract: Computer-based learning environments (CBLEs) present important opportunities for fostering learning; however, studies have shown that students have difficulty when learning with these environments. Research has identified that students' self-regulatory learning (SRL) processes may mediate the hypothesized positive relations between CBLEs and academic performance. In this review, we identified 33 empirical studies of SRL and CBLEs. We address three research questions: (1) How do learner and task characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
165
1
22

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 278 publications
(202 citation statements)
references
References 50 publications
3
165
1
22
Order By: Relevance
“…Therefore a question for further research is: to what extent can the affordances of blogs support cognitive, social and self-directed learning in the absence of additional face to face support? In their review of supporting self-regulated learning through computer based tools, (Winters, Greene, & Costich, 2008)report mixed evidence as to whether software support can be effective in this area. They note that some studies have found a discrepancy in students' self-reports of self-regulated learning while using support software and their actual usage of the relevant tools -students typically reported using software features to support self-regulated learning skills more frequently than the software log files indicated.…”
Section: Blogging Without Additional Face To Face Interactionsmentioning
confidence: 99%
“…Therefore a question for further research is: to what extent can the affordances of blogs support cognitive, social and self-directed learning in the absence of additional face to face support? In their review of supporting self-regulated learning through computer based tools, (Winters, Greene, & Costich, 2008)report mixed evidence as to whether software support can be effective in this area. They note that some studies have found a discrepancy in students' self-reports of self-regulated learning while using support software and their actual usage of the relevant tools -students typically reported using software features to support self-regulated learning skills more frequently than the software log files indicated.…”
Section: Blogging Without Additional Face To Face Interactionsmentioning
confidence: 99%
“…In addition to content learning, these agents are programmed to assist learning about different aspects of SRL, such as planning, goal-setting, metacognitive monitoring, strategy use, and reflection (see Azevedo & Aleven, 2013;Azevedo et al, 2012). The use of PAs can be effective for learners because research has shown that when students are provided with the appropriate scaffolding, this can help them to better learn (Kinnebrew et al, 2013), and more specifically to self-regulate their learning (Azevedo et al, 2012a;Graesser & McNamara, 2010;Winters et al, 2008). The role of prior knowledge is a critical individual differences variable that has not been adequately examined in the context of SRL and learning with multi-agent systems.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have also found that the mixture of cognitive and metacognitive scaffolding could enhance learners' cognitive skills (Berthold, Nuckles & Renkl, 2007;Zhang et al, 2015). Furthermore, a meta-analysis of 33 empirical studies in SRL within computer-based learning environments revealed that the characteristics of learners and the features of tasks (including the types of SRL supports) affect the quality of learners' SRL (Winters, Greene & Costich, 2008). Therefore, learners' characteristics and task features might be other factors influencing the effects of metacognitive scaffolding on self-regulated actions and cognitive performances.…”
Section: Cognitive Versus Metacognitive Scaffoldingmentioning
confidence: 99%